Study of the Polymerization of Methyl Methacrylate Initiated by Thioxanthone Derivatives: A Magnetic Field Effect - Keskin, Sevnur; Aydin, Meral; Khudyakov, Igor; Arsu, Nergis (Tubitak Scientific & Technological Research Council Turkey, 2009)
Free radical photopolymerization of methyl methacrylate (MMA) initiated by 2-mercaptothioxanthone (TX-SH), thioxanthone-thioacetic acid (TXSCH2COOH), and thioxanthone-carboxymethoxy acetic acid (TXOCH2COOH) as so called one-component initiators was performed with and without an external magnetic field (MF). These initiators contain light-absorbing and electron/hydrogen-donating fragments in one molecule and do not require an additional hydrogen donor, and initiate the polymerization of MMA in the air. Polymerization experiments were performed in solutions with 3 different optical densities at lambda 365 nm, where the photoinitiator absorbs. It was observed that application of MF leads to both larger conversion and higher molecular weight of the prepared PMMA, other conditions being equal. The effect of MF on the photopolymerization of MMA is discussed.
Keywords: Magnetic field effect; polymerization; photoinitiator; thioxanthone; one-component initiator; FREE-RADICAL POLYMERIZATION; STYRENE; ACID; Chemistry; Engineering